The final act of Juliette Willoughby : a novel - Lloyd, Ellery (Harper, an imprint of HarperCollinsPublishers, 2024)
Fifty years after runaway heiress artist Juliette Willoughby perished in an accidental studio fire in Paris, two Cambridge art history students stumble across proof that the fire was no accident, which threatens the very foundation of Juliette's aristocratic family and revives rumors of the infamous curse that has haunted them for generations.